2021
DOI: 10.1051/0004-6361/202140433
|View full text |Cite
|
Sign up to set email alerts
|

HCN (1−0) opacity of outflowing gas in Arp 220W

Abstract: Context. We present our findings for the HCN/H13CN 1−0 line ratio in the molecular outflow of Arp 220 west based on high-resolution ALMA data. Aims. Molecular gas masses in the outflowing gas of galaxies driven by active galactic nuclei or starbursts are important parameters for understanding the feedback of these latter two phenomena and star-formation quenching. The conversion factor of line luminosities to masses is related to the optical depth of the molecular lines. Methods. Using H13CN 1–0, the isotopic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…There is clear evidence for an embedded AGN in the western nucleus of Arp 220 (e.g Lockhart et al 2015;Rangwala et al 2015;Barcos-Muñoz et al 2018). A number of observations, including the detection of Fe Kα emission at 6.3 keV, support this conclusion (e.g., Yoast-Hull et al 2017;Wang et al 2021). Varenius et al (2016) further suggested that the alignment of the 150 MHz continuum morphology above and below the nuclear disk and the similarity to the 150 MHz observations of M82 are evidence for an outflow in the eastern nucleus, with the southern side being the closer (approaching) part consistent with CO (6-5) observations presented in Rangwala et al (2011).…”
Section: The Nuclear Disks Of Arp 220mentioning
confidence: 95%
“…There is clear evidence for an embedded AGN in the western nucleus of Arp 220 (e.g Lockhart et al 2015;Rangwala et al 2015;Barcos-Muñoz et al 2018). A number of observations, including the detection of Fe Kα emission at 6.3 keV, support this conclusion (e.g., Yoast-Hull et al 2017;Wang et al 2021). Varenius et al (2016) further suggested that the alignment of the 150 MHz continuum morphology above and below the nuclear disk and the similarity to the 150 MHz observations of M82 are evidence for an outflow in the eastern nucleus, with the southern side being the closer (approaching) part consistent with CO (6-5) observations presented in Rangwala et al (2011).…”
Section: The Nuclear Disks Of Arp 220mentioning
confidence: 95%
“…We obtain L ′ HCN = 6.03 × 10 6 K km s −1 pc 2 . The luminosity-to-mass conversion factor, α HCN , can vary from 0.24 to over 20 M ⊙ (K km s −1 pc 2 ) −1 (Barcos- Muñoz et al 2018;Evans et al 2020;Jones et al 2021), depending on the gas density and the line opacity (Jones et al 2021;Wang et al 2021). If we consider the standard extragalactic conversion factor α HCN of 10 M ⊙ (K km s −1 pc 2 ) −1 (Gao & Solomon 2004), M dg is calculated to be 6.03 × 10 7 M ⊙ .…”
Section: Mass Of Dense Molecular Gas In Cndsmentioning
confidence: 99%